Efficiency of adaptation to hypoxic hypoxia in a course of artificial climatetherapy in correction of the hormonal status at thyroid gland hypofunction at children - Radziejowska, Maria (Journal of Education, Health and Sport, 2018)
Stimulatory effect of artificial climatetherapy (intermittent hypoxic training) on the function of thyroid gland reveals not in increasing of different hormones during hypoxia only, but the improving of functional respiratory system (FRS) function by itself influences on endocrine system that is a part of regulatory chain of functional respiratory system by the children with hypothyroidism.